Natural detoxification capacity to inactivate nerve agents Sarin and VX in the rat blood - Bajgar, Jiří; Cabal, Jiří; Kassa, Jiří; Pavlík, Michal (Acta Medica, 2015)
BACKGROUND: The method of continual determination of the rat blood cholinesterase activity was developed to study the changes of the blood cholinesterases following different intervetions. AIMS: The aim of this study is registration of cholinesterase activity in the rat blood and its changes to demonstrate detoxification capacity of rats to inactivate sarin or VX in vivo. METHODS: The groups of female rats were premedicated (ketamine and xylazine) and cannulated to a. femoralis. Continual blood sampling (0.02 ml/min) and monitoring of the circulating blood cholinesterase activity were performed. Normal activity was monitored 1-2 min and then the nerve agent was administered i.m. (2×LD50). Using different time intervals of the leg compression and relaxation following the agent injection, cholinesterase activity was monitored and according to the inhibition obtained, detoxification capacity was assessed. RESULTS: Administration of sarin to the leg, then 1 and 5 min compression and 20 min later relaxation showed that further inhibition in the blood was not observed. On the other hand, VX was able to inhibit blood cholinesterases after this intervention. CONCLUSIONS: The results demonstrated that sarin can be naturally detoxified on the contrary to VX. Described method can be used as model for other studies dealing with changes of cholinesterases in the blood following different factors.
Keywords: Cholinesterase Inhibitors; Organophosphate Poisoning; Rats, Wistar; Inactivation, Metabolic; Cholinesterases; metabolická inaktivace; potkani Wistar; otrava organofosfáty; sarin; krysa rodu Rattus; Animals; ženské pohlaví; zvířata; Organothiophosphorus Compounds; Rats; Sarin; cholinesterasy; organothiofosforové sloučeniny; Female; cholinesterasové inhibitory